Developing Bilingual Press Release for Malang Creative Center - Arsita Dewi, Intan; Ulfah Hoesny, Mariana; Handayani, Tri Astuti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Communication is one of the important aspects of customer service; a company can be said to be a good company if it can provide quality customer service. One of the ways companies convey information to visitors is by making press releases. Malang Creative Center has problems in making press releases in two languages. As a result, Malang Creative Center does not have English-language information media aimed at foreign visitors. This research aims to develop a bilingual press release for Malang Creative Center. The press release contains information about what events are held and the latest information from Malang Creative Center. The design of this research is Design and Development Research (DDR). DDR ensures that press releases are systematically designed and developed based on empirical evidence and research findings. The method in this stage consists of five stages: analysis, design, development, implementation, and evaluation. At this stage, the researcher used several instruments, such as interviews and observations, to identify the problem. The researcher began to design the press release by organizing it step by step based on the information obtained. The next stage is the development stage, where researchers apply all concepts from the design stage and develop them into a press release. The next stage is the implementation stage, where the product is tested to expert validators. Then, the product is validated by expert validators, after which it is tested to the public in the evaluation stage. The results of this study are nineteen bilingual press releases published on the Malang Creative Center website that can provide information that visitors easily understand. Based on the questionnaire results, most respondents (47.5%) strongly agreed, and (52.5%) agreed that the information presented in the press releases was clear and easy to understand.